2017
DOI: 10.1097/ftd.0000000000000366
|View full text |Cite
|
Sign up to set email alerts
|

Azathioprine Therapy in a Pediatric TPMT-Deficient Patient—Still an Option

Abstract: We describe the case of a pediatric patient on azathioprine therapy with previously undiagnosed homozygote thiopurine S-methyltransferase (TPMT) deficiency, resulting in myelotoxic thiopurine metabolite levels. The patient was successfully treated with a very low azathioprine dose of 50 mg once a week (4% of standard dose), guided by frequent thiopurine metabolite measurement and a close clinical surveillance. We demonstrate that azathioprine therapy still might be an effective and safe therapeutic option in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A recent study suggested that enzyme-inducing antiepileptic drugs such as carbamazepine and oxcarbazepine might increase the apparent clearance of LEV by more than 40%. 27 In our cohort, only five women were treated with enzyme-inducing antiepileptic drugs. However, these women were already on stable polytherapy before pregnancy and no dose change was made during the pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that enzyme-inducing antiepileptic drugs such as carbamazepine and oxcarbazepine might increase the apparent clearance of LEV by more than 40%. 27 In our cohort, only five women were treated with enzyme-inducing antiepileptic drugs. However, these women were already on stable polytherapy before pregnancy and no dose change was made during the pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Especially patients with a homozygous genetic variant in TPMT (~0.3% of the population), and to a lesser degree patients with a heterozygous variant in TPMT (~10% of the population) are at increased risk for severe, life‐threatening, myelosuppression when treated with the standard recommended dose of azathioprine (AZA) or mercaptopurine (MP) . Leucopenia can be prevented by genotyping for these variants prior to initiation of thiopurine treatment and subsequently taper the thiopurine dose to 50% of the original dose in those heterozygous for a variant in TPMT and 0%‐10% of the original dose in patients with a homozygous variant . However, only up to 25% of the leucopenia cases can be explained by variants in TPMT , which makes that leucopenia is frequently observed in patients without a TPMT variant .…”
Section: Introductionmentioning
confidence: 99%